2013
DOI: 10.1097/aln.0b013e3182850da5
|View full text |Cite|
|
Sign up to set email alerts
|

Limb Remote Ischemic Preconditioning for Intestinal and Pulmonary Protection during Elective Open Infrarenal Abdominal Aortic Aneurysm Repair

Abstract: Limb RIPC attenuates intestinal and pulmonary injury in patients undergoing elective open infrarenal abdominal aortic aneurysm repair without any potential risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
105
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(110 citation statements)
references
References 44 publications
4
105
0
1
Order By: Relevance
“…This observation is in line with several other studies, for example, (Li et al. ). Whether the decrease in ROS is the mechanism underlying RIPC‐induced protection remains, however, unclear from these data.…”
Section: Discussionsupporting
confidence: 94%
“…This observation is in line with several other studies, for example, (Li et al. ). Whether the decrease in ROS is the mechanism underlying RIPC‐induced protection remains, however, unclear from these data.…”
Section: Discussionsupporting
confidence: 94%
“…Recently, a randomized controlled trial showed that remote IP powerfully counteracts the injury to the intestinal mucosa caused by a period of ischemia and subsequent reperfusion during elective open infrarenal abdominal aortic aneurysm repair [13] . Although intestinal protection with IP is a reproducible and powerful phenomenon, it has not been readily translated to routine clinical use.…”
Section: Discussionmentioning
confidence: 99%
“…Although restoration of blood flow to intestinal ischemic tissue is critical for tissue salvage, reperfusion also introduces inflammatory changes that exacerbate injury [12] . IP is a simple procedure conferring cytoprotection in critical organs that has clinical applications [13,14] . Although intestinal IP triggers powerful protective effects mechanisms by which it alleviates intestinal injury remain to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…After reperfusion is performed, in such cases, reactive oxygen species are generated and there is excess production of pro-inflammatory molecules and a subsequent inflammatory response, which can lead to damage to internal organs, such as the lungs, liver, kidneys, intestines and heart, as well as death [ 1 ] . Multiple organ dysfunction occurring after abdominal aortic surgery is one of the major causes of mortality and morbidity, with 25% of the deaths that occur after elective abdominal aortic repair being related to multiple organ dysfunction [ 2 ] . Silymarin, which is a mixture of flavonoids and polyphenols, has been shown to exhibit a variety of pharmacological activities as well as antioxidant, anti-inflammatory, immunomodulatory, hepatoprotective, neuroprotective, renoprotective [against ischemia-reperfusion (I/R) injury], gastroprotective, antibacterial, antiviral, antithrombotic, and vasodilatory effects in many experimental and clinical studies [ 3 , 4 ] .…”
Section: Introductionmentioning
confidence: 99%